Eksplorasi Nilai-Nilai Islam dalam Kurikulum di Era Digital: Studi di MAN 1 Blora - Kholil, Muhammad Abu (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
The development of the digital era presents opportunities and challenges in the integration of Islamic values ​​in education, especially in Islamic educational institutions. This study focuses on MAN 1 Blora as a case study to explore the application of Islamic values ​​in a technology-based curriculum. The main objective of this study is to examine the strategy of integrating Islamic values ​​in the curriculum in the digital era and to identify the challenges and solutions faced. This study uses a qualitative method with a case study approach. Data were collected through in-depth interviews, participatory observation, and document analysis, with data validation using triangulation techniques. The results of the study indicate that MAN 1 Blora has succeeded in integrating Islamic values ​​through a digital technology-based curriculum. Teachers utilize various platforms such as Google Classroom, YouTube, and social media to deliver Islamic material in an interesting and relevant way. In addition, digital-based habituation programs, such as online tadarus and Islamic literacy, also strengthen students' character building. However, there are significant challenges, including limited access to technology for some students and exposure to negative digital content that requires more intensive guidance from teachers. The discussion shows that digital technology provides a great opportunity to strengthen Islamic values, but requires a holistic approach involving infrastructure improvements, teacher training, and the development of interactive Islamic media. In conclusion, the integration of Islamic values ​​in the education curriculum in the digital era provides a significant contribution in forming an Islamic generation with strong character. MAN 1 Blora is a real example of the adaptation of Islamic educational institutions to the development of the times without abandoning Islamic values.